A recursive method to find the extreme and superstable curves in the parameter space of dissipative one-dimensional mappings - da Costa, Diogo Ricardo [UNESP]; de Paiva, Luam Silva [UNESP]; Rocha, Julia G. S. [UNESP]; Hermes, Joelson D. V.; Hansen, Matheus; Viana, Ricardo Luiz; Caldas, Iberê Luiz; Medrano-T, Rene O. [UNESP] (AIP Publishing, 2025)
This paper presents a recursive method for identifying extreme and superstable curves in the parameter space of dissipative one-dimensional maps. The method begins by constructing an Archimedean spiral with a constant arc length. Subsequently, it identifies extreme and superstable curves by calculating an observable ψ . The spiral is used to locate a region where ψ changes sign. When this occurs, a bisection method is applied to determine the first point on the desired superstable or extreme curve. Once the initial direction is established, the recursive method identifies subsequent points using an additional bisection method, iterating the process until the stopping conditions are met. The logistic-Gauss map demonstrates each step of the method, as it exhibits a wide variety of periodicity structures in the parameter space, including cyclic extreme and superstable curves, which contribute to the formation of period-adding structures. Examples of extreme and superstable curves obtained by the recursive method are presented. It is important to note that the proposed method is generalizable and can be adapted to any one-dimensional map.